1985
DOI: 10.1042/cs0680545
|View full text |Cite
|
Sign up to set email alerts
|

Antidiuretic hormone response to volume depletion in diabetic patients with cardiac autonomic dysfunction

Abstract: Thirty-three insulin-dependent diabetic patients were separated into two groups from the results of three different tests for cardiac vagal neuropathy: heart rate response to deep breathing, Valsalva manoeuvre and heart rate response to postural change. Seventeen patients were considered as without ('intact' patients) and 16 as with ('denervated' patients) cardiac autonomic dysfunction. One patient with a transplanted heart was also studied. Plasma antidiuretic hormone (ADH), plasma aldosterone and plasma reni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Each of these groups included seven subjects. All patients were tested for cardiac parasympathetic neuropathy using three non-invasive indices (deep breathing, Valsalva maneuver and lying to standing maneuver) as described in a previous study (Grimaldi, Pruszczynski, Thervet and Ardaillou 1985). There were more patients with vagal dysautonomia in group II (5) than in group I (2).…”
Section: Methodsmentioning
confidence: 99%
“…Each of these groups included seven subjects. All patients were tested for cardiac parasympathetic neuropathy using three non-invasive indices (deep breathing, Valsalva maneuver and lying to standing maneuver) as described in a previous study (Grimaldi, Pruszczynski, Thervet and Ardaillou 1985). There were more patients with vagal dysautonomia in group II (5) than in group I (2).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the possibility is not ruled out that the neurons from the medulla oblongata to the hypothalamus might be impaired in diabetic and non-diabetic neuropathies. Grimaldi et al (1985) and Reid et al (1989) reported that plasma AVP failed to increase in response to decreases in blood pressure, despite increases in heart rate in diabetic neuropathy with cardiac autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the AVP response to volume depletion has been reported to be attenuated in diabetic patients with cardiac dysfunction (Grimaldi et al 1985). On the other hand, it is shown that AVP plays an essential role in the prevention of orthostatic hypotension in diabetic autonomic insufficiency (Saad et al 1988; Zanella et al 1992).…”
mentioning
confidence: 99%